Hydroxynitrile lyase activity in non-commercialised plants - Kassim, Muhammad Arshad (My University, 2016)
Cyanogenesis is defined as the hydroxynitrile lyase catalysed release of a cyanide group in the form of hydrogen cyanide and the corresponding aldehyde or ketone. When a plant is attacked, the hydrogen cyanide released is a self-defence mechanism. A special characteristic of enzymatic reactions is that all enzymatic reactions are reversible - hydroxynitrile lyases can also be used for the synthesis of enantiomerically pure cyanohydrins which are of great importance in industry. In this study, the hydroxynitrile lyase activity of 102 plants from 41 families was investigated, first by screening for cyanogenic activity, followed by a hydroxynitrile lyase activity assay. Six plants were found to be cyanogenic and exhibited specific hydroxynitrile lyase activity: Adenia sp. (0.44 U/mg), Adenia firingalavensis (2.88 U/mg), Adenia fruticosa (1.99 U/mg), Adenia pechuelii (2.35 U/mg), Heywoodia lucens (1.76 U/mg) and Ximenia caffra (1.84 U/mg). This is the first report of hydroxynitrile lyase activity in these plants.
A dissertation submitted to the School of Molecular and Cell Biology, Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2015
Keywords: Cyanohydrins.